Implementation of an Integrated Management Information System to Create Business Efficiency - Awan Setiawan (Journal Of Data Science, 2023)
This research aims to investigate and analyze the application of Integrated Management Information Systems (IMIS) in the context of business organizations with the aim of increasing operational efficiency and resource management. This research uses a qualitative approach with descriptive methods. The research results show that the implementation of an Integrated Management Information System (IMIS) makes a positive contribution to business efficiency. With good integration between information systems, companies can optimize operational processes, reduce redundancy, and improve information flow. In addition, IMIS also supports faster and more accurate decision making, enabling companies to respond to market changes more efficiently. The research results also highlight the benefits of IMIS in strengthening relationships with customers through holistic access to customer information. This integration also helps in managing company resources efficiently and improves information security. In conclusion, IMIS implementation is a relevant and effective strategy in increasing the company's competitiveness and operational efficiency.